Psycho-social Climate and Its Influence on the Development of Communicative Competences in Students - Radojević, Tatjana S.; Kompirović, Tatjana P. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
As a fundamental institution of educational system, a school holds a student in the very core of its activities. Everything planned, organized or managed as a part of educational program and work is directly or indirectly in the function of students’ development and education. The best results in the development of communicative competences in students are accomplished through systematical educational work, pedagogically and didactically planned and realized. Through lecturing classes, as the most dominant module of educational work, students are being offered a way to develop and improve their communicative competence on a higher lever and in an adequate psycho-social environment, by learning from and being mentored by pedagogically expert lecturing staff. The results of numerous pedagogical and psychological studies are suggesting that communication between a teacher and a student is an important aspect of the quality of educational work, but also the indicator of psycho-social climate in the classroom. By monitoring the teacher-student communication, it is possible to determine the type of interpersonal relationship as well, and also the psycho-social climate that happens to be dominant in the class. The psycho-social climate in the class as one of the factors for development of students’ communicative competence is highly dependent on the teacher’s educational style. Various teaching styles (democratic, autocratic, anarchic, or permissive) and their influence on the development of communicative competences in students are being considered in this paper.